PENYULUHAN METODE PEMBUANGAN SAMPAH ORGANIK DAN SAMPAH NON ORGANIK BAGI RUMAH TANGGA DI LINGKUNGAN RW 03 DESA CISEMPUR, KEC. JATINANGOR - Fordian, Dian; Lavinia, Hanna Audrey; Rianto, Rendra; Azis, Esa Amirul (Universitas Padjadjaran, 2017)
ABSTRACTCommunity priorities (PPM OKK) performs a public garbage disposal methods of organic and non organic waste for households in Cisempur Village environmentalists RW 03, Kec. Jatinangor, Kab. Sumedang. This counseling of the target is the PKK cadres and administrator RW 03 Cisempur Village. The selection of the target audience based on the consideration that the inhabitants are the